Strategic capital budgeting : developing and implementing the corporate capital allocation program - Johnson, Hazel J. (Chicago, Ill. : Probus Pub. Co., 1994)
Helps answer vital questions about how to allocate your firm's long-term resources in plant, property and equipment. These purchases, typically the firm's largest investments, should not be left to guesswork. It brings financial-decision making tools within easy reach to every member of the management team.
Includes index.
oif 21/07/16
Loans
Keywords: Capital budget; Capital investments; Corporations; International business enterprises